Mayo Clinic wellness solutions for fibromyalgia [videorecording (DVD)] - Neukum, Cathe (Mayo Clinic ; Gaiam, Inc., 2007)
The symptoms of fibromyalgia - including widespread pain, fatigue and tenderness - are frustrating, but so is the fact that the cause is unknown and the symptoms can be off and on. Learn self-care tips and techniques that help ensure your fibromyalgia is more "off" than "on".--Producer.